Novel type IV secretion system involved in propagation of genomic islands. - Juhas, M; Crook, D; Dimopoulou, I; Lunter, G; Harding, R; Ferguson, D; Hood, D (2007)
Type IV secretion systems (T4SSs) mediate horizontal gene transfer, thus contributing to genome plasticity, evolution of infectious pathogens, and dissemination of antibiotic resistance and other virulence traits. A gene cluster of the Haemophilus influenzae genomic island ICEHin1056 has been identified as a T4SS involved in the propagation of genomic islands. This T4SS is novel and evolutionarily distant from the previously described systems. Mutation analysis showed that inactivation of key genes of this system resulted in a loss of phenotypic traits provided by a T4SS. Seven of 10 mutants with a mutation in this T4SS did not express the type IV secretion pilus. Correspondingly, disruption of the genes resulted in up to 100,000-fold reductions in conjugation frequencies compared to those of the parent strain. Moreover, the expression of this T4SS was found to be positively regulated by one of its components, the tfc24 gene. We concluded that this gene cluster represents a novel family of T4SSs involved in propagation of genomic islands.